Dose Comparison Using Thermoluminescent Dosimeters During Multislice Computed Tomography With Different Parameters for Simulated Spine Tumor Examination. Issue 2 (August 2018) - Hsieh, Chih-Chuan; Li, Chiao-Zhu; Lin, Meng-Chi; Yang, Yun-Ju; Hong, Kun-Ting; Chen, Yi-Hsun; Syu, Zih-Hsian; Ju, Da-Tong
Abstract : Abstract: This study aims to compare the effect of Philips' Brilliance 64‐slice and 256‐slice (multislice) computed tomography on effective doses when changing the operating parameters for simulated examinations of patients' spine tumors, including changes in pitch, tube voltage (kV), and effective tube current-time product (mA s). This study considers the possibility of using other probable operating conditions to reduce patients' effective doses. The absorbed doses to organs and skin are measured by taking data from thermoluminescent dosimeters (GR‐200 and GR‐200F) in relevant positions on the anthropomorphic Rando phantom. We also used an American College of Radiology computed tomography accreditation phantom to experiment with image spatial resolution under various scan conditions in order to achieve results over 5 line pairs per cm, the analytical capability required to meet diagnostic needs. The results show that, in general, when we change the pitch, effective tube current-time product, and tube voltage, the effective doses from 256‐slice computed tomography exceed those from 64‐slice computed tomography.